UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU FIQIH DI MADRASAH IBTIDAIYAH DARUL FIKRI TAHUN 2016-2017 - Anik Puspuani; Happy Susanto; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2017)
The data source in the research is the subject of which data can be obtained. In this study the main target data is the headmaster of Ibtidaiyah Darul Fikri and all Madrasah Ibtidaiyah Darul Fikri staff.The purpose of this study is to analyze the principals' efforts in improving the professionalism of fiqh teachers in the Madrasah Ibtidaiyah Darul Fikri Year of 2016-2017. To analyze the obstacles faced by the principals in improving the professionalism of fiqh teachers in the Madrasah Ibtidaiyah Darul Fikri Year 2016-2017. To find out what the principals do to improve the professionalism of fiqh teachers in the Madrasah Ibtidaiyah Darul Fikri Year of 2016-2017.The approach used by writer is qualitative with descriptive design, technique of data retrieval using observation method, interview method, documentation method.The results of the author's research, the head of the school's efforts in improving the professionalism of fiqh teachers is to include fiqh teachers in trainings, seminars, workshops and so forth. The obstacles faced by Madrasah Ibtidaiyah Darul Fikri's headmaster in improving the professionalism of fiqh teachers is the lack of knowledge of fiqh teachers in class management, lack of cooperation between fiqh teachers, lack of sense of responsibility. While the evaluation done by the headmaster of Ibtidaiyah Madrasah Darul Fikri The academic year 2016-2017 is a monthly evaluation meeting.Therefore, the headmaster's efforts are good, but it needs to be improved in terms of education in order to become a professional fiqh teacher.